Penerapan Unit Penyaring Air untuk Mendukung Ekowisata Isyo Hills di Kampung Repang Muaif, Distrik Nimbokrang, Kabupaten Jayapura - Marcelino N. Yonas; Hendra K. Maury; Leonard Siregar; Rosye H.R. Tanjung (LPPM Uncen, 2025)
Repang Muaif Village, located in Nimbokrang District, Jayapura Regency, has significant potential for ecotourism development. However, limited access to clean water remains a major challenge for the management of Isyo Hills Ecotourism. Surface water used by the community contains high levels of organic matter and sediment, resulting in murky water that affects visitor comfort. This community service project aimed to develop and implement a simple water filtration unit using gravity-based filtration techniques. The methodology included site surveys, technical training, and community-based construction of the filtration system using locally available materials. The results show significant improvement in water quality, particularly in turbidity and pH levels. The treated water became clearer, and its pH increased from 6.2 to 7.1, meeting acceptable standards for non-drinking daily use. This technology is easy to replicate and maintain, empowering local communities to sustainably manage clean water resources in support of eco-tourism activities.